Whistleblowing Intention in Accounting Students with Locus of Control as a Moderating Variable - Dwi Suhartini; Rizdina Azmiyanti; Sofie Yunida Putri (Universitas Hayam Wuruk Perbanas, 2022)
Academic fraud committed by accounting students is an important phenomenon to study. This study aims to examine the effect of professional commitment and achiavellian attitudes on whistleblowing intention with locus of control as a moderating variable. This study uses a quantitative approach. The subjects of the analysis are accounting students at state universities in Surabaya. Sampling is carried out using a non-probability sampling technique with quota sampling. Data collection is carried out using a mail survey via Google Forms. The collected data that can be processed are two hundred questionnaires. The analysis technique uses WarpPLS 8.0. The results of this study show that professional commitment has an effect on whistleblowing intention; Machiavellian attitude has an effect on whistleblowing intention; and locus of control is unable to moderate the effect of professional commitment and Machiavellian attitude on whistleblowing intention. The results prove that accounting students at state universities in Surabaya have high professional commitment and Machiavellian attitude in fighting academic fraud, even though this Machiavellian attitude is actually a negative attitude.